PENGEMBANGAN VIDEO PEMBELAJARAN INTERAKTIF MATA PELAJARAN IPAS PADA KURIKULUM MERDEKA DI KELAS IV SDN 09 SITIUNG - Anggrayni, M.; Putri, Suci Rahma; Fitriani, Fitriani (Dharmas Education Journal (DE_Journal), 2023)
This study aims to develop interactive learning videos using powerpoint applications in science learning in the Merdeka Curriculum class IV SDN 09 Sitiung. Because the results of observations and interviews with the homeroom teacher of class IV showed that the learning was low, learning videos really helped increase students' interest in learning with a total of 8 students. Research and Development (R&D) method in the ADDIE model which has important steps contained in it, namely: 1. The stage of needs analysis, student characteristics, and curriculum (Analyze) 2. learning design stage ( Design), 3. development stage is developing video products by testing validity in the form of questionnaires (language, content/construct, and graphics), by obtaining the percentage score from the three validators on average 85% in the "Very Valid" category, 4. implementation stage conducts practicality tests, product effectiveness on students and educators with teacher response questionnaires and student response questionnaires by obtaining percentage of 89% "Very Practical" category determines effectiveness of using student learning interest questionnaires after watching interactive learning videos (Implementation), with a percentage of 87% in the "Very Effective" category 5. evaluation stage where the stage knows the revisions made to product to develop learning from all the previous stages.